2008
DOI: 10.1021/ie800174c
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric Analysis of Copper Oxide for Chemical-Looping Hydrogen Generation

Abstract: The chemical-looping hydrogen generation (CLH) system consists of reduction of metal oxide and water decomposition by oxidizing reduced metal oxide. In the present study, water decomposition by the reduction and oxidation of metal oxide (CuO) was conducted in a thermogravimetric analysis (TGA) system for the CLH process. The particles are reduced completely in an atmosphere of synthesis gas (H2 + CO), and the fully reduced particles decompose water to produce 3.7 L of H2 per kilogram of metal oxide. The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In the 20-cycle test neither performance decay nor mechanical degradation of the oxygen carrier has been observed. Son et al [49] found that the oxygen particles supported on SiO 2 exhibit worse reactivity than those on Al 2 O 3 . In addition, ZrO 2 , TiO 2 , and bentonite were also studied as the inert support for copper-based oxygen carrier [50][51][52].…”
Section: Cuo-based Oxygenmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 20-cycle test neither performance decay nor mechanical degradation of the oxygen carrier has been observed. Son et al [49] found that the oxygen particles supported on SiO 2 exhibit worse reactivity than those on Al 2 O 3 . In addition, ZrO 2 , TiO 2 , and bentonite were also studied as the inert support for copper-based oxygen carrier [50][51][52].…”
Section: Cuo-based Oxygenmentioning
confidence: 99%
“…The outlet gas stream from the fuel reactor contains only CO 2 and H 2 O at complete conversion of the fuel, while the exit gas from the steam reactor is just H 2 with excess H 2 O. Therefore, pure H 2 and CO 2 can be obtained with H 2 O condensation without any further separation process [95]. The work in [95] reported that 3.7 L of H 2 was generated through reaction between per kilogram fully reduced copper-based oxide and steam.…”
Section: Chemical-looping Reforming (Clr) and Chemical-looping Hydrogmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced carrier is then transported to an air reactor where it is reconstituted to its original state with air. The CLWS process is based on two reactors, similar to those used in the CLC [11] with the difference that the desired product is hydrogen, not energy. A fuel (natural gas/syngas/ coal and even biomass) reacts with an oxygen carrier in the fuel reactor to produce both H 2 O and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Copper was recently proposed by Son et al as an active metal for H 2 generation [11]. The reaction occurs at low temperatures and involves the Cu/Cu 2 O redox couple Iron has probably been the most studied metal oxide (together with Zn/ZnO) regarding water hydrolysis.…”
Section: Introductionmentioning
confidence: 99%